PENDAMPINGAN DIGITAL MARKETING SEBAGAI UPAYA MENGEMBANGKAN USAHA BERBASIS TEKNOLOGI PADA HOME INDUSTRY - Kasmiati Kasmiati (Universitas Al-Amien Prenduan, 2022)
This community service activity aims to address marketing problems and improve the skills of home-based entrepreneurs in using technological assistance to market their products. Home-based businesses in Karanganyar Village require technology-based business development to be able to compete with their competitors. Observation and interviews were used to identify the use of social media. The methods used in assisting home-based businesses in digital marketing are in two ways, namely, through workshops and direct practice. An introduction to digital marketing, social media, and e-commerce, content marketing, digital management, digital marketing management, digital marketing FGD (forum group discussion), and evaluation are among the materials provided to assist technology-based business development through digital marketing. The results of this service can be seen from the results of the evaluation of participants, who gave very good responses on the grounds that mentoring activities provide insight, knowledge, and skills in marketing that are beneficial to program participants. Almost all of them want to practice digital marketing in their business. Advice that can be given in creating marketing content is to add attractive captions and hashtags that are easy to follow so that products are easy to find.